Corporate governance and non - performing loans: evidence from listed banks in Sri Lanka - Balagobei, S. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
Non-performing loans (NPLs) plays a significant role as they reflect the credit quality of the loan portfolio of banks, and in aggregate terms, reflect the credit quality of the loan portfolio of the banking sector in a country. The study aims to examine the influence of corporate governance on non-performing loans of listed banks in Sri Lanka for the period from 2013 to 2017. In this study, listed banks are selected as sample for the purpose of data analysis with help of Pearson’s correlation and multiple regressions. Secondary data from the annual reports of banks and journals was used for the analysis purpose. The findings show that board activities have a significant influence on non-performing loans of listed banks in Sri Lanka whereas other corporate governance variables such as board size, board independence and CEO duality have no significant influence on non-performing loans. This study would hopefully benefit to the academicians, researchers, policy-makers and practitioners of Sri Lanka and other similar countries.
Keywords: Corporate governance; Board activities; Non-performing loans